2013
DOI: 10.1080/01635581.2013.828089
|View full text |Cite
|
Sign up to set email alerts
|

Pinoresinol Inhibits Proliferation and Induces Differentiation on Human HL60 Leukemia Cells

Abstract: Pinoresinol (PIN), one of the simplest lignans, is the precursor of other dietary lignans that are present in whole-grain cereals, legumes, fruits, and other vegetables. Several experimental and epidemiological evidences suggest that lignans may prevent human cancer in different organs. In this study we investigated the chemopreventive properties of PIN on cell lines derived from different sites either expressing or not the functional tumor suppressor protein p53. It was found that PIN inhibited the proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…Moreover, olive polyphenols have been reported to reduce glycaemia and cholesterolemia [13]. Olive oil polyphenols have a beneficial effect on the cancer cell line model: in vitro studies reveal that pinoresinol inhibits the proliferation of colon and prostate tumor cells and induces apoptosis in human leukaemia cells [14] Oleuropein, in addition, is capable of preventing colon rectal cancer in mice [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, olive polyphenols have been reported to reduce glycaemia and cholesterolemia [13]. Olive oil polyphenols have a beneficial effect on the cancer cell line model: in vitro studies reveal that pinoresinol inhibits the proliferation of colon and prostate tumor cells and induces apoptosis in human leukaemia cells [14] Oleuropein, in addition, is capable of preventing colon rectal cancer in mice [15].…”
Section: Introductionmentioning
confidence: 99%
“…Sepporta et al [27] found that PINO inhibited the growth of MDA-MB-231, but not of MCF7 cells; however, their study was limited to 100 μM, which is not considered to be a physiological concentration. In contrast, we tested a wide range of PINO concentrations, ranging from 0.001 to 100 μM, and showed that low concentrations of PINO elicited a significant antiproliferative effect on both human breast tumour cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported anticancer effects of PINO by suppressing the expression of the lipogenic enzyme FASN in HER-2 overexpressing MCF7 cells [26]. Recently, Sepporta et al [27] observed that PINO inhibited the growth of MDA-MB-231 cells, but not of MCF7 cells. Importantly, no previous study has examined the effects of PINO on a normal human breast cell line, which would address whether PINO plays a protective role against cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…PIN was reported to inhibit cell proliferation and induce the differentiation of leukemia HL60 cells by inducing mRNA and protein overexpression of the CDK inhibitor CDKN1A (Sepporta et al 2013). PIN-rich olive oil has been tested in p53 depleted cancer cells (SW480 with p53 mutant) and p53 competent cancer cells (RKO and HCT116).…”
Section: Dietary Lignansmentioning
confidence: 99%